A novel multiplex PCR system for the detection of virulence associated genes of E. coli O157:H7 from food system - V, Puttalingamma; R, Shylaja; V, Batra H; S, Bawa A (Recent Research in Science and Technology, 2012)
In view of the importance E. coli serotype 0157:H7 in human diseases, an easy and quick system is desirable to detect toxin producing strains. In this report, we describe standardization of a novel multiplex Polymerase Chain Reaction (mPCR) assay for simultaneous detection of four important genes associated with the organism E. coli 0157:H7 viz., stx 1, stx 2, eae A, hly A along with an internal amplification control (IAC). The mPCR method developed in the present study is sensitive enough to detect cells as low as 103 CFU ml-1 or g-1 of the food samples. The E. coli 0157:H7 strains having been identified to contain the gene in the mPCR were unequivocally detected positive for the serological and conventional culture method. As E. coli 0157:H7 is qualified as biowarfare agent; this mPCR system is of immense help in detecting them during emergencies of biological war and suspected outbreaks.